ALGORITHM OF GUARANTEED-AND-ADAPTIVE CONTROL OF AEROSTATIC VEHICLE UNDER UNDETERMINED EXTERNAL TURBULENCES - Gusynin, Andriy; Tachinina, Helen (Proceedings of National Aviation University, 2014)
The guaranteed-and-adaptive algorithm of motion control of aerostatic vehicle are synthesized. It’s basedon differential transformation of initial mathematic model of differential game of airship motion and is morecomplicated in comparison with other algorithms. The obtained algorithm has the adaptation properties to turbulencesand provides a guarantee of aerostatic vehicle translation to the given states during the worst combination ofturbulence factors. The point of given algorithm is the achievement of lowest terminal errors during the process ofairship motion control at the action of turbulences.